1993
DOI: 10.1177/106342669300100202
|View full text |Cite
|
Sign up to set email alerts
|

Does the Relationship Between Poor Reading and Delinquency Hold for Males of Different Ages and Ethnic Groups?

Abstract: The study examines the relationship between reading and delinquency for three large community samples of first-, fourth-, and seventh-grade African-American and white boys. Reading was correlated with delinquency, independent of neighborhood, SES, ethnicity, and family involvement effects. Although more African-American boys were delinquent than white boys, the likelihood of delinquency for boys with lower reading performance was the same in each ethnic group. Older boys with poor reading performance did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Findings from this study support the commonly held view that cognitive delays and low academic achievement are associated with offending (Farrington, 2005;Maguin et al, 1993). This study found, however, that the relationships are complex: although low IQ is associated with low school achievement and school failure, factors that are largely independent of IQ also contribute to low academic achievement and school failure.…”
Section: Theoretical Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…Findings from this study support the commonly held view that cognitive delays and low academic achievement are associated with offending (Farrington, 2005;Maguin et al, 1993). This study found, however, that the relationships are complex: although low IQ is associated with low school achievement and school failure, factors that are largely independent of IQ also contribute to low academic achievement and school failure.…”
Section: Theoretical Implicationssupporting
confidence: 80%
“…Some studies suggest that intellectual disability and low academic achievement precede offending behaviour (Allerton et al, 2003;Farrington, 1995;Kenny et al, 2006;Maguin, Loeber, & LeMahieu, 1993;Vermeiren, De Clippele, Schwab-Stone, Ruchkin, & Deboutte, 2002). Some argue that juveniles with low school achievement develop fewer bonds with the school and community (Shochet, Dadds, Ham, & Montague, 2006).…”
mentioning
confidence: 96%
“…More specific links with reading problems have been much debated (Brier, 1989;Cornwell & Bawden, 1992). Wadsworth (1979), for example, found that associations between early reading scores and later offending largely reflected variations in social class and birth order, while Maguin, Loeber and LeMathieu (1993) identified attentional problems as a further 'third variable' that could account for reading performance-delinquency associations. In our own earlier study of reading retarded boys, rates of officially recorded juvenile delinquency were elevated, but not significantly so, among poor readers without behaviour problems (Maughan et al, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…However, an alternative explanation is that the association between school failure and delinquency may be noncausal and arise from common antecedent factors which are associated with both increased risks of academic problems and increased risks of delinquency (Hinshaw, 1992). These factors may include early disruptive behavior patterns (Fergusson, Horwood, & Lynskey, 1993;Maguin et al, 1993; Treml l l Fig. la.…”
mentioning
confidence: 93%
“…1969; Maguin, Loeber, & LeMahieu, 1993;Tracy, Wolfgang, & Figlio, 1990;Tremblay et al, 1992). The persistent association between academic achievement, learning delays, and delinquent behaviors has led to a search for an explanation of these associations.…”
mentioning
confidence: 97%